STABILITY OF CONTINUOUS WELDED RAIL UNDER A MOVING TRAIN - Novakovych, V. I. (Science and Transport Progress, 2003)
In article the new principle of calculation of a railway track without joints at stability is stated in view of the factor of time and influence of trains.